The physical demands of wheelchair tennis match play: a systematic review with meta-analysis - Williamson, S.; Ardern, C. L.; Berry, C.; Heron, N.; Janse van Rensburg, D. C.; Jansen, M. G. T.; McCormick, S.; Reid, M.; Sánchez-Pay, A.; Saueressig, T.; Schoonmade, L. J.; Shaw, R. B.; et al. (Sports Medicine, 2024)
Key Points